A Study on health issues related to the psychological impact of COVID - Paul, Rupa; Roy, Rupsha; Pandit, Abhijit; Chowdhury, Subhajit Basu (The journal of contemporary issues in business and government, 2023)
India had undergone “lockdown” since March 25, 2020. The pandemic has resulted in many psychological impacts in the form of reduced level of patience, acute depression, increased level of violence, loneliness and abnormal behavior with friends and peer groups, loss of zeal and vigor etc. The urban life of Kolkata is not exceptional from that and lots of changes are there in between normal and new normal. Our present study emphasizes traces of these changes in the overall urban lifestyle of Kolkata. Moreover, the study will help to analyze the outcome which might have brought any behavioral changes in individual or any other health issues in post COVID period along with the impact on family members, including children. An online survey was conducted through Google questionnaire and based on the online survey data tables are prepared after quantitative analysis. The economic lifestyle of urban people of Kolkata has resulted in accommodation of new habits and practices in between the time of normal and new normal.